Prospective evaluation of a patented DNA test for canine hip dysplasia (CHD). - Eberhard Manz; Bernd Tellhelm; Michael Krawczak (PLoS ONE)
Genetic testing has been propagated as a suitable means to specify individual risks for canine hip dysplasia (CHD). However, the current lack of validation of most genetic CHD tests has left dog owners and breeders in the dark about their practical utility. Therefore, the Society for German Shepherd Dogs (Verein für Deutsche Schäferhunde, SV) initiated a prospective study of 935 animals to assess independently the value of a genetic CHD test (European Patent Specification EP 2 123 777 B1) that was developed by Distl et al. (2009) on the basis of the SV animal stock. Dogs were followed-up for 3 years after birth, classified regarding their CHD phenotype using the scheme of the Fédération Cynologique Internationale, and genotyped for the 17 single nucleotide polymorphisms (SNPs) constituting the CHD test in question. Individual SNP genotypes were combined into animal-specific genomic breeding values (GBVs), calculated as the weighted sum of SNP-wise scores as laid down in the patent specification. Logistic regression analysis revealed that, unexpectedly, the odds ratio for CHD decreased, rather than increased, by a factor of 0.98 per unit increase of the GBV. Nevertheless, since this effect was not statistically significant (95% CI: 0.93-1.03), and the area-under-curve of the test was only 0.523, it must be concluded that the genetic test patented by Distl et al. (2009) is unsuitable for individual CHD risk assessment.